2019
DOI: 10.1093/gastro/goz046
|View full text |Cite
|
Sign up to set email alerts
|

The safety of esophagojejunostomy via a transorally inserted-anvil method vs extracorporeal anastomosis using a circular stapler during total gastrectomy for Siewert type 2 adenocarcinoma of the esophagogastric junction

Abstract: Abstract Background Intracorporeal esophagojejunostomy via a transorally inserted-anvil method during laparoscopic total gastrectomy (LTG) for upper gastric cancer has been demonstrated to be feasible, but the use of this assessment exclusively for Siewert type 2 adenocarcinoma of the esophagogastric junction (AEG) has not been reported. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…Schietroma et al reported an incidence of EJAL up to 14.6% [32]. For patients with Siewert type 2 adenocarcinoma of the esophagogastric junction, the incidence of EJAL in our center reached 13.5% [4]. Therefore, in the clinical setting, EJAL is regarded as one of the most critical postoperative complications.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Schietroma et al reported an incidence of EJAL up to 14.6% [32]. For patients with Siewert type 2 adenocarcinoma of the esophagogastric junction, the incidence of EJAL in our center reached 13.5% [4]. Therefore, in the clinical setting, EJAL is regarded as one of the most critical postoperative complications.…”
Section: Discussionmentioning
confidence: 56%
“…In recent years, although the overall incidence of gastric cancer (GC) has declined, the incidence rate of proximal GC has increased [1,2]. Surgical resection is the cornerstone of the treatment of advanced GC, and laparoscopic techniques are widely used due to their advantages, such as less invasiveness, rapid recovery, less bleeding and fewer complications [3][4][5][6][7][8][9]. At present, the feasibility of laparoscopic total gastrectomy (LTG) is still being explored, although the safety and effectiveness of laparoscopic radical gastrectomy for distal GC have been verified [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…All cases were reviewed by two pathologists, and histological diagnoses were confirmed without discrepancy. Clinical characteristics including age, body mass index (BMI), sex, diabetes (12), tumor location (13), histology, Lauren classification, grade, Tumor size, T stage (14), N stage (15,16), M stage (14), Ki-67 index, S-100, CD-31, D240, EBV, MMR, and, HER2 statuses, and routine blood indicators [white blood cell (WBC), mononuclear cell (MONO), eosinophilic granulocyte (EOS), neutrophil (NEU), lymphocyte (LYM), and platelet (PLT) counts, the neutrophil/lymphocyte ratio (NLR), and ABO blood group] were obtained from medical records, pathology reports, discharge summaries, and extracted from the prospective database. All procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national) and with the Helsinki Declaration of 1964 and later versions.…”
Section: Methods Tumor Specimens and Clinical Data Collectionmentioning
confidence: 99%
“…In recent years, laparoscopic technology has developed rapidly, and laparoscopic gastrectomy with D2 lymphadenectomy has been recognized by the world medical community. 4 - 7 How to regularly, thoroughly and safely perform laparoscopic lymphadenectomy for GC is crucial for the therapeutic effect and prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%